Temporal Sequencing of Mental Health Symptom Severity and Suicidal Ideation in Post-9/11 Men and Women Veterans Who Recently Separated from the Military - Karen A. Lawrence (SAGE Publishing, 2021)
Background Despite some evidence for gender differences in associations between military veterans’ mental health and suicidal ideation (SI), gender-specific prospective studies are lacking. The aims of this prospective study were to: (1) examine gender differences in veterans’ initial status and trajectories of mental health severity and SI status and (2) identify temporal sequencing of mental health predictors of SI. Methods Surveys of 1035 US veterans were administered at 3 time-points (T1, T2, T3) over a 7-year period following military separation, with an initial assessment within 2 years of military separation. Results Men reported higher baseline PTSD and alcohol misuse severity than women. No baseline gender difference in SI prevalence was detected. Baseline gender differences in mental health severity were maintained over time. For both men and women, remittance of SI was more likely from T1 to T2 than from T2 to T3 while chronic SI was more likely from T2 to T3. The strongest predictors of T3 SI were prior SI followed by alcohol misuse, depression, and PTSD severity with stronger effects for T2 predictors than T1. Conclusion The maintenance of baseline gender differences throughout trajectories of mental health predictors of SI supports the need for ongoing gender-specific mental health services. Current governmental interorganizational efforts are focused on suicide prevention during the first year after military service completion. Our findings indicate a need to extend mental health screening and treatment beyond the early post-military period to reduce risk and recurrence of SI for both men and women.